City mouse, country mouse: a mixed-methods evaluation of perceived communication barriers between rural family physicians and urban consultants in Newfoundland and Labrador, Canada. Issue 5 (6th May 2016) - Renouf, Tia; Alani, Sabrina; Whalen, Desmond; Harty, Chris; Pollard, Megan; Morrison, Megan; Coombs-Thorne, Heidi; Dubrowski, Adam
Abstract : Objectives: To examine perceived communication barriers between urban consultants and rural family physicians practising routine and emergency care in remote subarctic Newfoundland and Labrador (NL). Design: This study used a mixed-methods design. Quantitative and qualitative data were collected through exploratory surveys, comprised of closed and open-ended questions. The quantitative data was analysed using comparative statistical analyses, and a thematic analysis was applied to the qualitative data. Participants: 52 self-identified rural family physicians and 23 urban consultants were recruited via email. Rural participants were also recruited at the Family Medicine Rural Preceptor meetings in St John's, NL. Setting: Rural family physicians and urban consultants in NL completed a survey assessing perceived barriers to effective communication. Results: Data confirmed that both groups perceived communication difficulties with one another; with 23.1% rural and 27.8% urban, rating the difficulties as frequent (p=0.935); 71.2% rural and 72.2% urban as sometimes (p=0.825); 5.8% rural and 0% urban acknowledged never perceiving difficulties (p=0.714). Overall, 87.1% of participants indicated that perceived communication difficulties impacted patient care. Primary trends that emerged as perceived barriers for rural physicians were time constraints and misunderstanding of site limitations. Urban consultants' perceived barriers were inadequate patient information and lack of native language skills. Conclusions: Barriers to effective communication are perceived between rural family physicians and urban consultants in NL.